Epoxy alloy powder coating and preparation method and application thereof
By using a specific formula of zinc-aluminum-magnesium alloy powder and epoxy resin-combined epoxy alloy powder on metal devices of water surface photovoltaic power stations, the problem that the prior art is difficult to use in the marine environment for a long time is solved, and efficient corrosion resistance and aging resistance are achieved.
Patent Information
- Application Number
- CN202211098162.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2022-09-08
- Publication Date
- 2025-02-28
- Estimated Expiration
- 2042-09-08
AI Technical Summary
The existing technology is difficult to use in harsh environments such as the ocean for a long time, and cannot meet the 25-year service life requirements of surface photovoltaic power plants.
Epoxy alloy powder coating is prepared by combining a specific formula of zinc-aluminum-magnesium alloy powder with epoxy resin to improve the salt spray corrosion resistance and cycle aging resistance of the coating.
It has achieved effective protection of metal devices of water surface photovoltaic power stations in the marine environment, extended the service life of photovoltaic rods, and reduced maintenance costs.
Smart Images

Figure SMS_2 
Figure SMS_3
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of metal protective materials, and specifically relates to an epoxy alloy powder coating and a preparation method and application thereof. Background Art
[0002] Rods are an important part of water-surface photovoltaic power stations, which support and bear the photovoltaic modules, floating bodies and other equipment. Because metals are prone to corrosion failure in the ocean or other environments with high corrosion levels, water-surface photovoltaic power stations cannot be in such environments for a long time.
[0003] In the prior art, the metal rods of the water surface photovoltaic power station are generally made of galvanized, stainless steel or aluminum alloy, etc. The above materials cannot be used in the marine environment for a long time and do not meet the 25-year service life requirement of the water surface photovoltaic power station.
[0004] For example, CN104831205A discloses a method for anti-corrosion treatment of photovoltaic panel frames, which includes sequential steps of cleaning, drying, hot-dip galvanizing and cooling. The hot-dip galvanizing step is to heat the zinc liquid to 455-480°C, place the photovoltaic panel frame in the zinc liquid for 1-1.5 minutes and then take it out, and the zinc liquid contains 0.07-0.1% aluminum by mass; the process route is simple and is beneficial to the anti-corrosion quality of the photovoltaic panel frame surface. However, the process is still galvanizing on the metal surface, which is not suitable for long-term use in marine environments.
[0005] CN106784418A discloses an anti-corrosion treatment layer and its application in lithium battery soft packaging materials, wherein the anti-corrosion treatment layer comprises an alternating composite layer and a polymer layer, wherein the composite layer is formed by mixing a water-soluble resin and a chromium passivation solution and then drying, and the polymer layer is formed by curing a cationic polymer under the action of a crosslinking agent; by using specific materials to form the alternating composite layer and the polymer layer, the anti-corrosion treatment layer has excellent corrosion resistance while ensuring interlayer peeling strength and punching depth. However, the corrosion resistance of the treatment layer needs to be further improved and is not suitable for use in harsh environmental conditions such as the ocean.
[0006] CN108373755A discloses an anti-corrosion and wear-resistant metal powder coating, which includes E42 epoxy resin, zinc powder, copper powder, polyethylene wax, pigment, filler, accelerator, wear-resistant additive and antioxidant. The coating has a simple manufacturing process and a simple raw material structure, and antioxidants and wear-resistant additives are added to enhance the anti-corrosion and wear-resistant capabilities of the metal powder, making it convenient for industrial production. However, the corrosion resistance is poor, and it is also not suitable for use in harsh environments such as the ocean.
[0007] Therefore, developing an anti-corrosion coating with good corrosion resistance that can permanently protect surface photovoltaic devices used in the ocean is an urgent problem to be solved in this field. Summary of the invention
[0008] In view of the shortcomings of the prior art, the purpose of the present invention is to provide an epoxy alloy powder coating and a preparation method and application thereof. The epoxy alloy powder coating is compounded with a zinc-aluminum-magnesium alloy powder of a specific formula and an epoxy resin, which can improve the salt spray corrosion resistance and cyclic aging resistance of the coating, and has a higher self-corrosion potential and a lower self-corrosion current density, and can effectively protect the metal components of the water surface photovoltaic power station.
[0009] To achieve this object, the present invention adopts the following technical solutions:
[0010] In a first aspect, the present invention provides an epoxy alloy powder coating, which comprises, by weight, 20 to 50 parts of epoxy resin and 40 to 80 parts of zinc-aluminum-magnesium alloy powder; the mass percentage of zinc in the zinc-aluminum-magnesium alloy powder is ≥50%.
[0011] In the present invention, the zinc-aluminum-magnesium alloy powder is mainly composed of zinc, which is matched with magnesium and aluminum to form an epoxy alloy powder coating with epoxy resin. The epoxy alloy powder coating has excellent corrosion resistance, a higher self-corrosion potential and a lower self-corrosion current density. The coating can effectively protect metal devices used in water surface photovoltaic power stations, meet the anti-corrosion requirements of the marine environment, extend the service life of photovoltaic poles, and reduce maintenance costs.
[0012] Preferably, the epoxy alloy powder coating includes 20 to 50 parts of epoxy resin in parts by weight, for example, 22 parts, 24 parts, 26 parts, 28 parts, 30 parts, 32 parts, 34 parts, 36 parts, 38 parts, 40 parts, 42 parts, 44 parts, 46 parts, 48 parts, etc.
[0013] Preferably, the epoxy alloy powder coating includes 40 to 80 parts of zinc-aluminum-magnesium alloy powder, in parts by weight, for example, 42 parts, 44 parts, 46 parts, 48 parts, 50 parts, 52 parts, 54 parts, 56 parts, 58 parts, 60 parts, 62 parts, 64 parts, 66 parts, 68 parts, 70 parts, 72 parts, 74 parts, 76 parts, 78 parts, etc.
[0014] In the present invention, when the epoxy resin and the zinc-aluminum-magnesium alloy powder are within specific contents, the coating has a better anti-corrosion effect; a higher content of the epoxy resin or a lower amount of the zinc-aluminum-magnesium alloy powder will result in reduced salt spray corrosion resistance and cyclic aging resistance of the coating.
[0015] Preferably, the mass percentage of zinc in the zinc-aluminum-magnesium alloy powder is ≥50%, for example, it can be 52%, 54%, 56%, 58%, 60%, 62%, 64%, 66%, 68%, 70%, 72%, 74%, 76%, 78%, 80%, 82%, 84%, 86%, 88%, 90%, 92%, 94%, 96%, 98% and the like.
[0016] Preferably, the zinc-aluminum-magnesium alloy powder includes, by mass percentage, 1.5-3.5% aluminum (for example, 1.6%, 1.7%, 1.8%, 1.9%, 2%, 2.1%, 2.2%, 2.3%, 2.4%, 2.5%, 2.6%, 2.7%, 2.8%, 2.9%, 3%, 3.1%, 3.2%, 3.3%, 3.4%, etc.), 1-2% magnesium (for example, 1.05%, 1.1%, 1.15%, 1.2%, 1.25%, 1.3%, 1.35%, 1.4 %, 1.45%, 1.5%, 1.55%, 1.6%, 1.65%, 1.7%, 1.75%, 1.8%, 1.85%, 1.9%, 1.95%, etc.) and 94-97.5% zinc (for example, it can be 94.2%, 94.4%, 94.6%, 94.8%, 95%, 95.2%, 95.4%, 95.5%, 95.6%, 95.8%, 96%, 96.2%, 96.4%, 96.6%, 96.8%, 97%, 97.2%, 97.4%, etc.).
[0017] In the present invention, when the content of each component in the zinc-aluminum-magnesium alloy powder is within a specific range, the anti-corrosion effect of the coating is better; if the percentage of zinc, magnesium or aluminum in the zinc-aluminum-magnesium alloy powder is too much or too little, the salt spray corrosion resistance and cyclic aging resistance of the coating will be reduced.
[0018] Preferably, the zinc-aluminum-magnesium alloy powder also includes a fourth component.
[0019] Preferably, the fourth component includes any one of silicon, indium or rare earth metals, or a combination of at least two of them.
[0020] Preferably, the rare earth metal includes at least one of cerium, scandium, yttrium, lanthanum, praseodymium, neodymium, promethium, samarium, europium, gadolinium, terbium, dysprosium, holmium, erbium, thulium, ytterbium or lutetium.
[0021] Preferably, the mass percentage of the fourth component in the zinc-aluminum-magnesium alloy powder is 0.01-0.3%, for example, it can be 0.02%, 0.04%, 0.06%, 0.08%, 0.1%, 0.12%, 0.14%, 0.16%, 0.18%, 0.2%, 0.22%, 0.24%, 0.26%, 0.28%, etc.
[0022] Preferably, the zinc-aluminum-magnesium alloy powder comprises flaky zinc-aluminum-magnesium alloy powder.
[0023] In the present invention, the use of flaky zinc-aluminum-magnesium alloy powder can enable the coating to be stacked on the metal surface, extending the erosion path of oxygen and water, and having a better shielding effect, which is beneficial to improving the corrosion resistance of the coating.
[0024] Preferably, the thickness of the flaky zinc-aluminum-magnesium alloy powder is less than 1 μm, for example, it can be 0.25 μm, 0.3 μm, 0.35 μm, 0.4 μm, 0.45 μm, 0.5 μm, 0.55 μm, 0.6 μm, 0.65 μm, 0.7 μm, 0.75 μm, 0.8 μm, 0.85 μm, 0.9 μm, 0.95 μm, etc.
[0025] In the present invention, the thickness of the flaky zinc-aluminum-magnesium alloy powder is within a specific range, so that the corrosion resistance of the coating is better; when the thickness is greater than 1 μm, the flaky structure is not conducive to forming a lamellar structure, and its corrosion resistance effect is reduced.
[0026] In the present invention, the thickness measurement method of the flaky zinc-aluminum-magnesium alloy powder is measured by referring to the lamination method (Guan Junfang, Bai Cuiping, Zhu Yingbo, et al. Study on the sample preparation method for the thickness determination of flaky ultrafine powder [J]. China Powder Technology, 2010, 16(4):3.).
[0027] Preferably, the fineness of the zinc-aluminum-magnesium alloy powder is 1000-5000 mesh, for example, it can be 1200 mesh, 1400 mesh, 1500 mesh, 1600 mesh, 1800 mesh, 2000 mesh, 2200 mesh, 2400 mesh, 2600 mesh, 2800 mesh, 3000 mesh, 3200 mesh, 3400 mesh, 3600 mesh, 3800 mesh, 4000 mesh, 4200 mesh, 4400 mesh, 4600 mesh, 4800 mesh, etc.
[0028] Preferably, the fineness of the zinc-aluminum-magnesium alloy powder is 2000-5000 mesh.
[0029] In the present invention, the fineness of the zinc-aluminum-magnesium alloy powder is within a specific range, so that the corrosion resistance of the coating is better; if the fineness is too small or too large, the corrosion resistance is poor.
[0030] In the present invention, the zinc-aluminum-magnesium alloy powder is prepared by the following method, which comprises:
[0031] The zinc-aluminum-magnesium alloy powder is obtained by mixing and melting metal zinc, metal aluminum and metal magnesium and atomizing them.
[0032] In the present invention, the metal zinc, metal aluminum and metal magnesium are pure zinc, pure aluminum and pure magnesium respectively.
[0033] Preferably, the mixed material further comprises a fourth component.
[0034] Preferably, the melting equipment is a vacuum melting furnace.
[0035] Preferably, the melting is carried out in a protective atmosphere.
[0036] Preferably, the protective atmosphere comprises nitrogen and / or argon.
[0037] Preferably, the melting temperature is 500-700°C, for example, 550°C, 600°C, 650°C, etc.
[0038] Preferably, the atomization equipment is a vacuum atomization system.
[0039] Preferably, after the atomization, the atomized powder is mixed with a grinding aid, ground until the alloy powder thickness is less than 1 μm, centrifugally screened to obtain an alloy powder with a fineness of 1000 to 5000 mesh, and dried to obtain the zinc-aluminum-magnesium alloy powder.
[0040] Preferably, the mass ratio of the atomized powder to the grinding aid is (1-1.5):(2-4), wherein the specific values in (1-1.5) can be, for example, 1, 1.1, 1.2, 1.3, 1.4, etc.; the specific values in (2-4) can be, for example, 2.2, 2.5, 2.8, 3, 3.2, 3.5, 3.8, etc.
[0041] Preferably, the epoxy alloy powder coating further comprises 2 to 5 parts of film-forming aids, such as 2.5 parts, 3 parts, 3.5 parts, 4 parts, 4.5 parts, etc., by weight.
[0042] Preferably, the film-forming aid comprises ethylene glycol.
[0043] Preferably, the epoxy alloy powder coating further comprises 0.2 to 0.8 parts of dispersant, for example, 0.3 parts, 0.4 parts, 0.5 parts, 0.6 parts, 0.7 parts, etc., in parts by weight.
[0044] Preferably, the dispersant includes at least one of anionic dispersants, cationic dispersants, nonionic dispersants or amphoteric dispersants.
[0045] Preferably, the epoxy alloy powder coating further comprises 0.2 to 2 parts of defoaming agent, for example, 0.4 parts, 0.6 parts, 0.8 parts, 1 parts, 1.2 parts, 1.4 parts, 1.6 parts, 1.8 parts, etc., in parts by weight.
[0046] Preferably, the defoaming agent includes but is not limited to PA-311.
[0047] Preferably, the epoxy alloy powder coating further comprises 0.2 to 1 parts of thickener, for example, 0.4 parts, 0.6 parts, 0.8 parts, etc., by weight.
[0048] Preferably, the thickener comprises carboxymethyl cellulose and / or hydroxymethyl cellulose.
[0049] Preferably, the solid content of the epoxy alloy powder coating is 88-99%, for example, it can be 88.2%, 88.4%, 88.6%, 88.8%, 89%, 89.5%, 90%, 91%, 92%, 93%, 94%, 95%, 96%, 97%, 98%, etc.
[0050] In a second aspect, the present invention provides a method for preparing the epoxy alloy powder coating according to the first aspect, the preparation method comprising:
[0051] The epoxy resin is mixed with zinc-aluminum-magnesium alloy powder to obtain the epoxy alloy powder coating.
[0052] Preferably, the mixing is performed in a solvent.
[0053] Preferably, the solvent comprises water.
[0054] Preferably, the mixed material further comprises any one of a film-forming aid, a dispersant, a defoaming agent or a thickener, or a combination of at least two thereof.
[0055] Preferably, the mixing time is 60 to 100 min, for example, 65 min, 70 min, 75 min, 80 min, 85 min, 90 min, 95 min, etc.
[0056] As a preferred technical solution of the present invention, the preparation method comprises: mixing the solvent, dispersant and film-forming aid for 5 to 15 minutes, adding epoxy resin and mixing for 25 to 35 minutes, then adding zinc-aluminum-magnesium alloy powder and mixing for 35 to 45 minutes, and finally adding defoamer and thickener, stirring thoroughly to obtain the epoxy alloy powder coating.
[0057] Preferably, the rotation speed of mixing the solvent, dispersant and film-forming aid is 1500-2500 rpm, for example, 1800 rpm, 2000 rpm, 2200 rpm, 2400 rpm, etc.
[0058] Preferably, the speed of mixing the epoxy resin is 600-1200 rpm, for example, 800 rpm, 1000 rpm, 1100 rpm, etc.
[0059] Preferably, the rotation speed of the mixing of the zinc-aluminum-magnesium alloy powder is 300-500 rpm, for example, 350 rpm, 400 rpm, 450 rpm, etc.
[0060] In a third aspect, the present invention provides an anti-corrosion coating, the anti-corrosion coating comprising a base layer and a surface layer stacked in sequence. The coating of the base layer comprises the epoxy alloy powder coating as described in the first aspect.
[0061] Preferably, the thickness of the bottom layer is 50-400 μm, for example, 70 μm, 100 μm, 150 μm, 200 μm, 250 μm, 300 μm, 350 μm, 380 μm, etc.
[0062] Preferably, the coating of the surface layer includes silicone coating and / or polyurethane coating.
[0063] Preferably, the thickness of the surface layer is 100-400 μm, for example, 100 μm, 150 μm, 200 μm, 250 μm, 300 μm, 350 μm, 380 μm, etc.
[0064] In the present invention, the preparation method of the anti-corrosion coating comprises: applying the epoxy alloy powder coating to a metal substrate to obtain the base layer; applying the surface layer coating to the side of the base layer away from the metal substrate to obtain the anti-corrosion coating.
[0065] Preferably, the epoxy alloy powder coating is applied to the metal substrate in two steps.
[0066] In the present invention, the preparation method of the anti-corrosion coating is carried out according to the method of GB / T1727-1992.
[0067] In a fourth aspect, the present invention provides an application of the epoxy alloy powder coating as described in the first aspect and / or the anti-corrosion coating as described in the third aspect in metal protection for water surface photovoltaic power stations.
[0068] The numerical range described in the present invention not only includes the point values listed above, but also includes any point values between the above numerical ranges that are not listed. Due to space limitations and for the sake of simplicity, the present invention no longer exhaustively lists the specific point values included in the range.
[0069] Compared with the prior art, the present invention has the following beneficial effects:
[0070] The epoxy alloy powder coating provided by the present invention uses zinc-aluminum-magnesium alloy powder with zinc as the main body and is compounded with epoxy resin, which can improve the salt spray corrosion resistance and cyclic aging resistance of the coating, and has a higher self-corrosion potential and a lower self-corrosion current density, and can effectively protect the metal devices of the water surface photovoltaic power station. DETAILED DESCRIPTION
[0071] The technical solution of the present invention is further described below by specific implementation methods. It should be understood by those skilled in the art that the embodiments are only to help understand the present invention and should not be regarded as specific limitations of the present invention.
[0072] Preparation Example 1
[0073] A zinc-aluminum-magnesium alloy powder comprises, by mass percentage, 2.5% aluminum, 1.5% magnesium and 96% zinc; the zinc-aluminum-magnesium alloy powder is flaky zinc-aluminum-magnesium alloy powder with a flake thickness of 0.5 μm and a fineness of 2000 meshes.
[0074] A method for preparing zinc-aluminum-magnesium alloy powder, the method comprising:
[0075] Pure zinc, pure aluminum and pure magnesium are placed in a vacuum melting furnace, and nitrogen is introduced for gas protection at a temperature of 650°C. After the melting is completed, a zinc-aluminum-magnesium alloy molten liquid is obtained, and atomized zinc-aluminum-magnesium alloy powder is obtained through a vacuum atomization system; the obtained zinc-aluminum-magnesium alloy powder is mixed with a grinding aid (BASF grinding aid of Shanghai Kaiyin Chemical Co., Ltd.) 963) was ground in a grinding jar at a mass ratio of 1:2 at a rotation speed of 500 rpm for 30 min, and then separated by a centrifuge to obtain an alloy powder with a fineness of 2000 mesh, which was then vacuum dried for 12 h to obtain the flaky zinc-aluminum-magnesium alloy powder.
[0076] Preparation Example 2
[0077] A zinc-aluminum-magnesium alloy powder comprises, by mass percentage, 1.5% aluminum, 1% magnesium, 0.2% silicon and 97.3% zinc; the zinc-aluminum-magnesium alloy powder is flaky zinc-aluminum-magnesium alloy powder with a flake thickness of 0.4 μm and a fineness of 3000 meshes.
[0078] A method for preparing zinc-aluminum-magnesium alloy powder, wherein the rotation speed is 600 rpm, after grinding for 30 minutes, the alloy powder with a fineness of 3000 mesh is centrifugally screened, and the other steps and parameters are the same as those in Preparation Example 1.
[0079] Preparation Example 3
[0080] A zinc-aluminum-magnesium alloy powder comprises, by mass percentage, 3.5% aluminum, 2% magnesium, 0.05% cerium and 94.45% zinc; the zinc-aluminum-magnesium alloy powder is flaky zinc-aluminum-magnesium alloy powder with a flake thickness of 0.2 μm and a fineness of 5000 mesh.
[0081] A method for preparing zinc-aluminum-magnesium alloy powder, wherein the rotation speed is 700 rpm, after grinding for 40 minutes, the alloy powder with a fineness of 5000 mesh is centrifugally screened, and the other steps and parameters are the same as those in Preparation Example 1.
[0082] Preparation Example 4
[0083] A zinc-aluminum-magnesium alloy powder, which differs from Preparation Example 1 only in that, measured by mass percentage, the zinc-aluminum-magnesium alloy powder includes 5% aluminum, the ratio of magnesium to zinc remains unchanged, and other parameters are the same as those of Preparation Example 1.
[0084] A method for preparing zinc-aluminum-magnesium alloy powder, wherein the specific steps are the same as those of Preparation Example 1.
[0085] Preparation Example 5
[0086] A zinc-aluminum-magnesium alloy powder, which differs from Preparation Example 1 only in that, measured by mass percentage, the zinc-aluminum-magnesium alloy powder includes 1% aluminum, the ratio of magnesium to zinc remains unchanged, and other parameters are the same as those of Preparation Example 1.
[0087] A method for preparing zinc-aluminum-magnesium alloy powder, wherein the specific steps are the same as those of Preparation Example 1.
[0088] Preparation Example 6
[0089] A zinc-aluminum-magnesium alloy powder, which differs from Preparation Example 1 only in that, measured by mass percentage, the zinc-aluminum-magnesium alloy powder includes 0.5% magnesium, the ratio of aluminum to zinc remains unchanged, and other parameters are the same as those of Preparation Example 1.
[0090] A method for preparing zinc-aluminum-magnesium alloy powder, wherein the specific steps are the same as those of Preparation Example 1.
[0091] Preparation Example 7
[0092] A zinc-aluminum-magnesium alloy powder, which differs from Preparation Example 1 only in that, measured by mass percentage, the zinc-aluminum-magnesium alloy powder includes 4% magnesium, the ratio of aluminum to zinc remains unchanged, and other parameters are the same as those of Preparation Example 1.
[0093] A method for preparing zinc-aluminum-magnesium alloy powder, wherein the specific steps are the same as those of Preparation Example 1.
[0094] Preparation Example 8
[0095] A zinc-aluminum-magnesium alloy powder, which is different from Preparation Example 1 only in that the sheet thickness of the zinc-aluminum-magnesium alloy powder is 1.5 μm, and other parameters are the same as those of Preparation Example 1.
[0096] A method for preparing zinc-aluminum-magnesium alloy powder. In the preparation method, the grinding speed is 400 rpm and the time is 20 min; the other steps and parameters are the same as those in Preparation Example 1.
[0097] Preparation Example 9
[0098] A zinc-aluminum-magnesium alloy powder, which is different from Preparation Example 1 only in that the fineness of the zinc-aluminum-magnesium alloy powder is 1500 mesh, and other parameters are the same as those of Preparation Example 1.
[0099] A method for preparing zinc-aluminum-magnesium alloy powder, wherein the alloy powder is centrifugally screened to a fineness of 1500 mesh, and other steps and parameters are the same as those in Preparation Example 1.
[0100] Comparative Preparation Example 1
[0101] A zinc-aluminum-magnesium alloy powder, which differs from Preparation Example 1 only in that, measured by mass percentage, the zinc-aluminum-magnesium alloy powder includes 45% zinc, the ratio of aluminum to magnesium remains unchanged, and other parameters are the same as those of Preparation Example 1.
[0102] A method for preparing zinc-aluminum-magnesium alloy powder, wherein the specific steps are the same as those of Preparation Example 1.
[0103] Comparative Preparation Example 2
[0104] A zinc-aluminum-magnesium powder, which differs from Preparation Example 1 only in that the preparation method does not include a step of obtaining a zinc-aluminum-magnesium alloy powder, but simply mixes zinc powder, magnesium powder and aluminum powder with the same content, and the other steps and parameters are the same as those in Preparation Example 1.
[0105] Comparative Preparation Example 3
[0106] A zinc-aluminum alloy powder, which differs from Preparation Example 1 only in that the alloy powder does not contain magnesium, the mass ratio of zinc to aluminum remains unchanged, and other steps and parameters are the same as those of Preparation Example 1.
[0107] In the present invention, the thickness of the alloy powder or metal powder provided in the preparation examples 1 to 9 and the comparative preparation examples 1 to 3 is characterized by a reference lamination method through a scanning electron microscope.
[0108] In the present invention, unless otherwise specified, the materials used in all embodiments and comparative examples are as follows:
[0109] Epoxy resin: Mitsui Chemicals (Shandong) Co., Ltd. 128 epoxy resin (E51)
[0110] Film-forming aid: Ethylene glycol, Nanjing Rongji Chemical Co., Ltd., polyester grade 99.9%
[0111] Dispersant: Guangdong Jiaming Chemical Co., Ltd. CM-3191
[0112] Defoamer: Foshan Nanhai Datian Chemical Co., Ltd. PA-311
[0113] Thickener: Carboxymethyl cellulose, Feicheng Hongrui Fine Materials Factory
[0114] Example 1
[0115] The present embodiment provides an epoxy alloy powder coating, which includes, by weight, 23 parts of epoxy resin, 70 parts of zinc-aluminum-magnesium alloy powder (Preparation Example 1), 0.7 parts of dispersant, 2.5 parts of ethylene glycol, 0.5 parts of defoaming agent, 0.3 parts of carboxymethyl cellulose and 3 parts of deionized water.
[0116] This embodiment provides a method for preparing an epoxy alloy powder coating, and the specific steps include:
[0117] Deionized water, dispersant and ethylene glycol were added into a disperser, stirred at 2000 rpm for 10 min, epoxy resin was added, dispersed at 1000 rpm for 30 min, zinc-aluminum-magnesium alloy powder was added, stirred at 500 rpm for 40 min, defoamer and carboxymethyl cellulose were added, stirred thoroughly, and mixed evenly to obtain the epoxy alloy powder coating.
[0118] Example 2
[0119] The present embodiment provides an epoxy alloy powder coating, which includes, by weight, 28 parts of epoxy resin, 63 parts of zinc-aluminum-magnesium alloy powder (Preparation Example 2), 0.6 parts of dispersant, 4.3 parts of ethylene glycol, 0.6 parts of defoaming agent, 0.5 parts of carboxymethyl cellulose and 3 parts of deionized water.
[0120] This embodiment provides a method for preparing an epoxy alloy powder coating, and the specific steps are the same as those in Embodiment 1.
[0121] Example 3
[0122] The present embodiment provides an epoxy alloy powder coating, which includes, by weight, 31 parts of epoxy resin, 60 parts of zinc-aluminum-magnesium alloy powder (Preparation Example 3), 0.5 parts of dispersant, 3 parts of ethylene glycol, 0.8 parts of defoaming agent, 0.7 parts of carboxymethyl cellulose and 4 parts of deionized water.
[0123] This embodiment provides a method for preparing an epoxy alloy powder coating, and the specific steps are the same as those in Embodiment 1.
[0124] Example 4
[0125] The present embodiment provides an epoxy alloy powder coating, which includes, by weight, 37 parts of epoxy resin, 55 parts of zinc-aluminum-magnesium alloy powder (Preparation Example 1), 0.5 parts of dispersant, 2.5 parts of ethylene glycol, 1 part of defoaming agent, 0.8 parts of carboxymethyl cellulose and 3.2 parts of deionized water.
[0126] This embodiment provides a method for preparing an epoxy alloy powder coating, and the specific steps are the same as those in Embodiment 1.
[0127] Example 5
[0128] The present embodiment provides an epoxy alloy powder coating, which includes, by weight, 40 parts of epoxy resin, 50 parts of zinc-aluminum-magnesium alloy powder (Preparation Example 1), 0.5 parts of dispersant, 3 parts of ethylene glycol, 1 part of defoaming agent, 1 part of carboxymethyl cellulose and 4.5 parts of deionized water.
[0129] This embodiment provides a method for preparing an epoxy alloy powder coating, and the specific steps are the same as those in Embodiment 1.
[0130] Example 6
[0131] This embodiment provides an epoxy alloy powder coating, which differs from Embodiment 1 only in that the zinc-aluminum-magnesium alloy powder is the zinc-aluminum-magnesium alloy powder provided in Preparation Example 4, and the other components, amounts and preparation methods are the same as those in Embodiment 1.
[0132] Example 7
[0133] This embodiment provides an epoxy alloy powder coating, which differs from Embodiment 1 only in that the zinc-aluminum-magnesium alloy powder is the zinc-aluminum-magnesium alloy powder provided in Preparation Example 5, and the other components, amounts and preparation methods are the same as those in Embodiment 1.
[0134] Example 8
[0135] This embodiment provides an epoxy alloy powder coating, which differs from Example 1 only in that the zinc-aluminum-magnesium alloy powder is the zinc-aluminum-magnesium alloy powder provided in Preparation Example 6, and the other components, amounts and preparation methods are the same as those in Example 1.
[0136] Example 9
[0137] This embodiment provides an epoxy alloy powder coating, which differs from Example 1 only in that the zinc-aluminum-magnesium alloy powder is the zinc-aluminum-magnesium alloy powder provided in Preparation Example 7, and the other components, amounts and preparation methods are the same as those in Example 1.
[0138] Example 10
[0139] This embodiment provides an epoxy alloy powder coating, which differs from Example 1 only in that the zinc-aluminum-magnesium alloy powder is the zinc-aluminum-magnesium alloy powder provided in Preparation Example 8, and the other components, amounts and preparation methods are the same as those in Example 1.
[0140] Embodiment 11
[0141] This embodiment provides an epoxy alloy powder coating, which differs from Example 1 only in that the zinc-aluminum-magnesium alloy powder is the zinc-aluminum-magnesium alloy powder provided in Preparation Example 9, and the other components, amounts and preparation methods are the same as those in Example 1.
[0142] Comparative Example 1
[0143] This comparative example provides an epoxy alloy powder coating, which differs from Example 1 only in that the zinc-aluminum-magnesium alloy powder is replaced with an equal amount of zinc powder, and the other components, amounts and preparation methods are the same as those in Example 1.
[0144] Comparative Example 2
[0145] This comparative example provides an epoxy alloy powder coating, which differs from Example 1 only in that the zinc-aluminum-magnesium alloy powder is the zinc-aluminum-magnesium alloy powder provided in Comparative Preparation Example 1, and the other components, amounts and preparation methods are the same as those in Example 1.
[0146] Comparative Example 3
[0147] This comparative example provides an epoxy alloy powder coating, which differs from Example 1 only in that the zinc-aluminum-magnesium alloy powder is the zinc-aluminum-magnesium powder provided in Comparative Preparation Example 2, and the other components, amounts and preparation methods are the same as those in Example 1.
[0148] Comparative Example 4
[0149] This comparative example provides an epoxy alloy powder coating, which differs from Example 1 only in that the zinc-aluminum-magnesium alloy powder is the zinc-aluminum alloy powder provided in Comparative Preparation Example 3, and the other components, amounts and preparation methods are the same as those in Example 1.
[0150] Application Example 1
[0151] A corrosion-resistant coating, comprising a base layer and a surface layer stacked in sequence; the coating of the base layer comprises the epoxy alloy powder coating provided in Example 1, and the thickness of the base layer is 70 μm; the coating of the surface layer is a silicone elastic coating (manufacturer: Shenzhen Xishun Silicone Technology Co., Ltd.; brand: XS-G1201), whose main components include terminal hydroxyl polydimethylsiloxane, calcium carbonate and pigment, etc., and the thickness of the surface layer is 100 μm.
[0152] The preparation method of the anti-corrosion coating comprises: applying the epoxy alloy powder coating to tinplate, brushing twice, and applying a surface coating after drying to obtain the anti-corrosion coating.
[0153] Application Example 2
[0154] A corrosion-resistant coating, comprising a base layer and a surface layer stacked in sequence; the coating of the base layer comprises the epoxy alloy powder coating provided in Example 2, and the base layer has a thickness of 70 μm; the surface layer comprises PU500 acrylic polyurethane topcoat (manufacturer: Tianjin Shuangshi Paint Co., Ltd.), and the surface layer has a thickness of 100 μm.
[0155] The preparation method of the anti-corrosion coating is the same as that of Application Example 1.
[0156] Application Example 3
[0157] A corrosion-resistant coating, comprising a base layer and a surface layer stacked in sequence; the coating of the base layer comprises the epoxy alloy powder coating provided in Example 3, and the base layer has a thickness of 70 μm; the coating of the surface layer is a silicone elastic coating (manufacturer: Shenzhen Xishun Silicone Technology Co., Ltd.; brand: XS-G1201), and the surface layer has a thickness of 100 μm.
[0158] The preparation method of the anti-corrosion coating is the same as that of Application Example 1.
[0159] Application Examples 4 to 11
[0160] In the present invention, the anti-corrosion coatings provided in Application Examples 4 to 11 differ from those in Application Example 1 only in that the bottom coating is the epoxy alloy powder coating provided in Examples 4 to 11, and the other components, parameters and preparation methods are the same as those in Application Example 1.
[0161] Comparative application example 1
[0162] An anti-corrosion coating, which differs from Application Example 1 only in that the bottom coating is the epoxy alloy powder coating provided in Comparative Example 1, and other components, parameters and preparation methods are the same as those in Application Example 1.
[0163] Comparative Application Example 2
[0164] An anti-corrosion coating, which differs from Application Example 1 only in that the bottom coating is the epoxy alloy powder coating provided in Comparative Example 2, and other components, parameters and preparation methods are the same as those in Application Example 1.
[0165] Comparative Application Example 3
[0166] An anti-corrosion coating, which differs from comparative application example 1 only in that the anti-corrosion coating has no surface layer, and other components, parameters and preparation methods are the same as those of comparative application example 1.
[0167] Comparative Application Examples 4-5
[0168] In the present invention, the anti-corrosion coating provided in comparative application examples 4 to 5 is different from that in application example 1 only in that the bottom coating is the epoxy alloy powder coating provided in comparative examples 3 to 4, and the other components, parameters and preparation methods are the same as those in application example 1.
[0169] Performance Testing
[0170] The test method is as follows:
[0171] (1) Salt spray resistance: Refer to the national standard "GB / T 10125-2021 Artificial atmosphere corrosion test salt spray test".
[0172] (2) Cyclic aging resistance: Refer to the international standard "ISO 12944 Paints and varnishes-Protective coating systems for corrosion protection of steel structures"
[0173] (3) Bottom current density and bottom open circuit potential: Apply an appropriate amount of epoxy alloy powder coating on the surface of a 10*10 mm square piece. After the surface coating is cured, use conductive tape to connect the back of the sample to the copper wire, and seal the sample with cold mounting, leaving 1 cm 2 The experiment used a CHI604e electrochemical workstation to test the electrochemical properties of the coating sample. The test system was a three-electrode system, in which the auxiliary electrode was a 3×3cm platinum electrode, the reference electrode was a saturated calomel electrode, and the working electrode was the sample to be tested, with an exposed area of 1cm 2 The corrosion medium used was a NaCl solution with a pH of 7 and a concentration of 3.5 (wt.%).
[0174] The specific test results are shown in Table 1:
[0175] Table 1
[0176]
[0177]
[0178] As can be seen from the above table, the epoxy alloy coating provided by the present invention is compounded with a zinc-aluminum-magnesium alloy and an epoxy resin of a specific formula, so that the anti-corrosion coating has excellent corrosion resistance and cyclic aging resistance, and has a higher self-corrosion potential and a lower self-corrosion current density. As can be seen from Application Examples 1 to 5, the salt spray resistance time of the anti-corrosion coating is 4500 to 5000 hours, the cyclic aging resistance time is 4000 to 4200 hours, and the primer current density is 1.23 to 5.41 μA / cm 2 , the open circuit potential of the primer is -1.1 to -0.85 V; and in a more preferred embodiment of the present invention, the salt spray resistance time of the anti-corrosion coating reaches 5000 h, the cycle aging resistance time reaches 4200 h, and the current density of the primer is 1.23 μA / cm 2 , the primer open circuit potential is -1.01V.
[0179] By comparing Application Example 1 with Application Examples 6 to 9, it can be seen that the content of magnesium or aluminum in the zinc-aluminum-magnesium alloy is not within a specific range, and the corrosion resistance of its coating is reduced; by comparing Application Example 1 with Application Examples 10 to 11, it can be seen that the sheet thickness or fineness of the zinc-aluminum-magnesium alloy is not within a specific range, the salt spray resistance and cyclic aging resistance time of its coating are shortened, and the corrosion resistance is deteriorated.
[0180] From the comparison between Application Example 1 and Comparative Application Example 1, it can be seen that when the zinc-aluminum-magnesium alloy powder is all zinc powder, the salt spray resistance time and the cycle aging test time of the coating are greatly shortened, and the current density of the primer is significantly increased; from the comparison between Application Example 1 and Comparative Application Example 2, it can be seen that when the zinc content in the zinc-aluminum-magnesium alloy powder is less than 50%, the salt spray resistance time and the cycle aging test time of the coating are greatly shortened, and the current density of the primer is increased; from the comparison between Comparative Application Example 1 and Comparative Application Example 3, it can be seen that when there is no surface layer in the anti-corrosion coating, the salt spray resistance time and the cycle aging test time of the coating are shortened. From Application Example 1 and Comparative Application Examples 4 to 5, it can be seen that the zinc-aluminum-magnesium alloy powder is just a simple mixture of metal powders, or is not a specific zinc-aluminum-magnesium metal combination, and the corrosion resistance of its coating is reduced.
[0181] In summary, the epoxy alloy powder coating provided by the present invention is compounded with flaky zinc-aluminum-magnesium alloy powder of specific formula, thickness and fineness and epoxy resin, and then used in combination with a surface coating, so that the anti-corrosion coating has excellent salt spray corrosion resistance and cyclic aging resistance, and has a higher self-corrosion potential and a lower self-corrosion current density. Applying it to surface photovoltaic metal poles and brackets can significantly improve the corrosion resistance of the substrate and has strong competitiveness.
[0182] The specific embodiments described above further illustrate the objectives, technical solutions and beneficial effects of the present invention in detail. It should be understood that the above description is only a specific embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principles of the present invention should be included in the protection scope of the present invention.
Claims
1. An anti-corrosion coating, characterized in that: The anti-corrosion coating comprises a bottom layer and a surface layer stacked in sequence; The coating of the bottom layer includes epoxy alloy powder coating; In parts by weight, the epoxy alloy powder coating comprises 20 to 50 parts of epoxy resin and 40 to 80 parts of zinc-aluminum-magnesium alloy powder; The zinc-aluminum-magnesium alloy powder comprises, in terms of mass percentage, 1.5-3.5% aluminum, 1-2% magnesium and 94-97.5% zinc; The zinc-aluminum-magnesium alloy powder includes flaky zinc-aluminum-magnesium alloy powder; The thickness of the flaky zinc-aluminum-magnesium alloy powder is less than 1 μm; the fineness of the zinc-aluminum-magnesium alloy powder is 2000-5000 mesh; The anti-corrosion coating has a salt spray resistance time of 4500-5000 hours, a cycle aging resistance time of 4000-4200 hours, and a bottom current density of 1.23-5.41 μA / cm 2 , the bottom open circuit potential is -1.1~-0.85V.
2. The anti-corrosion coating according to claim 1, characterized in that: The zinc-aluminum-magnesium alloy powder also includes a fourth component.
3. The anti-corrosion coating according to claim 2, characterized in that: The fourth component includes any one of silicon, indium or rare earth metals, or a combination of at least two of them.
4. The anti-corrosion coating according to claim 2, characterized in that: The mass percentage of the fourth component in the zinc-aluminum-magnesium alloy powder is 0.01-0.3%.
5. The anti-corrosion coating according to claim 1, characterized in that: The preparation method of the epoxy alloy powder coating comprises: The epoxy resin is mixed with zinc-aluminum-magnesium alloy powder to obtain the epoxy alloy powder coating.
6. The anti-corrosion coating according to claim 1, characterized in that: The thickness of the bottom layer is 50-400 μm.
7. The anti-corrosion coating according to claim 1, characterized in that: The coating of the surface layer includes silicone coating and / or polyurethane coating.
8. The anti-corrosion coating according to claim 1, characterized in that: The thickness of the surface layer is 100-400 μm.
9. Use of the anti-corrosion coating according to any one of claims 1 to 8 in metal protection for water surface photovoltaic power stations.
Citation Information
Patent Citations
Photovoltaic plate frame corrosion resistance treatment method
CN104831205A
Anticorrosive treatment layer and application thereof in lithium battery soft package material
CN106784418A
Anti-corrosive wear-resistant metal powder coating
CN108373755A
Zinc alloy anticorrosive paint
CN107216697A
Method for producing powdery coating material and method for producing coated iron member
JP2008303276A